The incidence of ALK inhibitor-related pneumonitis in advanced non-small-cell lung cancer patients: A systematic review and meta-analysis. (June 2019) - Suh, Chong Hyun; Kim, Kyung Won; Pyo, Junhee; Hatabu, Hiroto; Nishino, Mizuki
Highlights: The overall incidence of ALK inhibitor pneumonitis was 2.14% in advanced NSCLC. Patients from Japanese cohorts had a higher incidence of ALK-inhibitor pneumonitis. Further studies of mechanisms and risk factors of ALK pneumonitis are needed. Abstract: Introduction: We evaluated the incidence of pneumonitis in clinical trials of anaplastic lymphoma kinase (ALK) inhibitors in patients with advanced non-small cell lung cancer (NSCLC) and compared the incidence among different cohorts, in order to identify possible predisposing factors for ALK inhibitor-related pneumonitis. Methods: MEDLINE and EMBASE search up to 1/30/18 using the keywords, "alectinib", "ceritinib", "crizotinib", "brigatinib", and "lung cancer", resulting in a total of 20 eligible cohorts with 2261 patients treated with ALK inhibitor monotherapy for advanced NSCLC. The pooled incidences of all-grade, high-grade, and grade 5 pneumonitis were calculated. Subgroup analyses were conducted with meta-regression using study-level covariates. Results: The overall pooled incidence of pneumonitis was 2.14% (95% CI: 1.37–3.34) for all grade, 1.33% (95% CI: 0.80–2.21) for high grade, and 0.22% (95% CI: 0.09-0.52) for grade 5 pneumonitis. The incidence was significantly higher in studies from Japan compared to studies of non-Japan origin, for all-grade (6.25% vs 1.14%, p  < 0.001) and high-grade pneumonitis (3.31% vs 0.39%, p  < 0.001). Multivariate meta-regression demonstrated the cohorts from Japanese studies had significantly higher odds of pneumonitis for all-grade (odds ratio [OR]: 4.329 [95% CI: 1.918, 9.770], p  < 0.001) compared to those of non-Japan origin, after adjusting for types of ALK inhibitors. Conclusions: The overall incidence of ALK inhibitor pneumonitis was 2.14% in patients with advanced NSCLS. The patients from Japanese cohorts had a higher incidence of ALK-inhibitor pneumonitis, which indicates the need for increased awareness and caution for pneumonitis in Japanese patients treated with ALK inhibitors.